Mechanical Properties of Strengthening 5083-H111 Aluminum Alloy Plates at Elevated Temperatures - Abuzaid, Wael (2021)
The use of aluminum alloys for external strengthening of reinforced concrete (RC) beams has been capturing research interest. Exposure to harsh environmental conditions can severely impact the strengthening efficiency. This works aims to investigate the degradation in the mechanical properties of aluminum alloy AA 5083 plates when exposed to temperatures ranging from 25 to 300 °C. Quasi-static Isothermal tensile experiments were conducted at different temperatures. It was observed from the experimental results that the yield strength remained constant in the temperature range of 25–150 °C before starting to drop beyond 150 °C, with a total reduction of ≈ 40% at 300 °C. The elastic modulus was temperature sensitive with about 25% reduction at 200 °C before experiencing a significant and pronounced reduction at 300 °C. The percentage drops in stiffness and yield strength at 300 °C were 62.8% and 38%, respectively. In addition, the Mechanical Threshold Strength Model (MTS) parameters were established to capture the yield strength temperature dependence. Two analytical models were developed based on the experimental results. Both models can reasonably predict the elastic modulus and yield strength of AA 5083 plates as a function of temperature. It was concluded that AA plates should be properly insulated when used as externally bonded reinforcement to strengthen RC beams.